Water availability, water content and chemical treatment of seeds on the emergence of soybean seedlings - Renato Téo de Barros; Cibele Chalita Martins; Givanildo Zildo da Silva; Tatiane Sanches Jeromini (Revista Ciência Agronômica)
ABSTRACT During the germination process, seeds are susceptible to abiotic and biotic stresses, such as attacks by pests and pathogens. In this context, chemical treatment of seeds can promote physiological and morphological changes in seeds and seedlings, in addition to protecting seeds. Two experiments were conducted with the following objectives: (I) assess the effect of soybean seed water content on seedling emergence under different water availability conditions; (II) assess the effect of chemical treatment of soybean seeds on seedling emergence under water stress conditions. In the first experiment, seeds of four cultivars had their water content adjusted to 8, 11, and 14% and were sown in soil under four water potential levels (-0.01; -0.02; -0.10 and -0.40 MPa). In the second experiment, seeds of the same cultivars were treated using metalaxyl, fludioxonil and thiamethoxam, and untreated seeds were used as controls. Sowing was carried out in soil under four water potentials, and seed quality parameters were evaluated in both experiments. The data subjected to analysis of variance, and the means were compared using the Tukey test at 5% probability level. There is no restriction on sowing soybean seeds with water content between 8 and 14% when the soil is under full water availability. Under conditions of soil water restriction, it is recommended to use seeds with water content between 11 and 14%. Under water deficit conditions, treated soybean seeds show better membrane maintenance and superior performance in seedling emergence.